Da educação de usuários à construção de competência em informação no contexto das bibliotecas das universidades federais: um estudo a partir da Universidade Federal de Alagoas e Universidade Federal de Minas Gerais - Marcos Aurélio Gomes (2016)
With this study, we intend to have a better comprehension of information literacy development in the context of libraries in Brazilian universities. The main goal was to analyze the contributions of actions and/or activities for users education inside libraries and/or online promoted by libraries of Brazilian universities associated to federal institutions of higher education. We studied the process of information literacy formation in students/users, aiming the construction of autonomous and aware individuals when conducting the process of search for and use of information in society. We validate this research by its insertion in the conceptual approaches of Library Science and Information Science, as researching users education in university libraries in the perspective of building information literacy is to investigate the inter-relations of access, use, and information needs associated to students/users in society. It is an exploratory study, using survey as method. We researched two universities: Universidade Federal de Alagoas, and Universidade Federal de Minas Gerais. We performed data analysis with quantitative and qualitative approaches. The tools used were a questionnaire and (Web) content analysis. The questionnaire was applied in 2,133 undergraduate students of all different subjects and in 31 librarians/library managers. With students, we verified perceptions regarding knowledge or abilities in information acquired through the actions/activities for users education. With librarians/library managers, the questionnaire apprehended aspects related to the understanding of available users education services and to the users study mechanisms adopted to propose such services. The (Web) content analysis allowed us to build a synoptic table, that served as a base for data classification of online and offline available services in the websites of the researched university libraries. It also allowed the identification of potential services in the process of information literacy, and, therefore, the acquisition of information regarding the existence of tutorials, search for information procedures, and trainings. We conclude that users education, developed in university libraries, needs a new (re)signification to contribute with information literacy of classroom courses of undergraduate students.